2021
DOI: 10.1111/bjep.12448
|View full text |Cite
|
Sign up to set email alerts
|

Control and value appraisals and online multiple‐text comprehension in primary school: The mediating role of boredom and the moderating role of word‐reading fluency

Abstract: Background. Online multiple-text comprehension is a key skill of the 21st Century, yet the study of its relations with boredom in young students has been disregarded. Boredom is an achievement emotion expected to be predicted negatively by antecedents like control and value appraisals and to be associated to a negative performance. Notwithstanding its documented domain-specificity, scarce attention has been paid to investigating these relations with primary-school students in the reading domain, and specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 88 publications
(172 reference statements)
3
9
0
Order By: Relevance
“…Students with higher levels of interest reported lower levels of boredom than their less interested peers. These associations were found for boredom in mathematics as well as in German class and provide further empirical support that students' interest is critically important for students' boredom in primary school (see Putwain et al 2018;Raccanello et al 2022).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Students with higher levels of interest reported lower levels of boredom than their less interested peers. These associations were found for boredom in mathematics as well as in German class and provide further empirical support that students' interest is critically important for students' boredom in primary school (see Putwain et al 2018;Raccanello et al 2022).…”
supporting
confidence: 57%
“…Although the beginning of formal schooling is enormously important for students' emotional experience of learning and schooling, empirical research that has investigated academic boredom, its causes, and its consequences during primary school is still scarce . The assumptions of control-value theory concerning the importance of control and value appraisals for academic boredom should be as relevant in primary school as previously demonstrated for older samples (see, e.g., Putwain et al 2021;Raccanello et al 2022). Already in primary-schoolaged children, boredom has been found to be negatively associated with intrinsic value and control appraisals (Putwain et al 2021) as well as academic achievement (Raccanello et al 2019).…”
Section: Academic Boredom In Primary Schoolmentioning
confidence: 84%
See 1 more Smart Citation
“…While educational psychologists have long been interested in the research of academic motivation, it is only recently that they have been interested in the study of academic emotions [ 1 ]. The cognitive-motivational paradigm focuses on academic emotions that have a favorable or negative influence on academic results, such as achievement, motivation, and deep-level cognitive learning techniques [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature on boredom during the COVID-19 pandemic in postsecondary settings is still developing, research on students ranging from primary school to college levels, who were forced to homeschool as a result of the pandemic, found that students who were highly prone to boredom perceived their homeschooling to be more challenging, which subsequently lowered their adherence to learning at home [ 9 ]. Thus, boredom likely has a negative impact on students’ learning in at-home and online learning settings [ 10 ], making it an important emotion to study during the COVID-19 pandemic, which has forced many students to learn remotely.…”
Section: Introductionmentioning
confidence: 99%